A robust PID like state-feedback control via LMI approach: An application on a double inverted pendulum system - Delibasi, Akin; Kucukdemiral, Ibrahim B.; Cansever, Galip (IEEE, 2007)
This paper addresses the design method for robust PIID like controllers which guarantee the quadratic stability, performance in terms of H-2 and H-infinity specifications, pole locations and maximum output control. The approach is based on the transformation of the PID controller design problem to that of state feedback controller design thereby the convex optimization approaches can be adapted. Real time experimental results on a double inverted pendulum system demonstrates the validity and applicability of the proposed approach.
Keywords: DESIGN; Automation & Control Systems; Robotics